2020
DOI: 10.1099/jmm.0.001195
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibitory effect of statins on planktonic cells and biofilms of the Sporothrix schenckii species complex

Abstract: Introduction. Sporotrichosis, caused by species of the Sporothrix schenckii complex, is the most prevalent subcutaneous mycosis in many areas of Latin America. Statins are a class of drugs widely used for lowering high sterol levels through their action on 3-hydroxy-3-methylglutaryl-CoA reductase, a key enzyme in the synthesis of sterol. Aim. In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…To make their architectural differences visible, untreated and chitosan-treated mixed biofilms were evaluated by scanning electron microscopy (SEM), 26 with minor modifications. Biofilms were formed directly on Thermanox™ coverslips using 12-well tissue culture plates.…”
Section: Methodsmentioning
confidence: 99%
“…To make their architectural differences visible, untreated and chitosan-treated mixed biofilms were evaluated by scanning electron microscopy (SEM), 26 with minor modifications. Biofilms were formed directly on Thermanox™ coverslips using 12-well tissue culture plates.…”
Section: Methodsmentioning
confidence: 99%
“…The colony counts in both Groups 1 and 2 were statistically lower than the control group with a colony count of 9.23E+06 CFU/ml. Brilhante et al 33 studied the effect of Simvastatin on cutaneous Sporotrichosis which showed that Sporothrix biofilms were inhibited by the statin in vitro. This can be translated clinically where the use of a systemic antifungal is not preferred, such as in pregnancy.…”
Section: Topical Statinsmentioning
confidence: 99%
“…Brilhante et al 33 . studied the effect of Simvastatin on cutaneous Sporotrichosis which showed that Sporothrix biofilms were inhibited by the statin in vitro .…”
Section: Clinical Applicationsmentioning
confidence: 99%
“…Supporting this theory, simvastatin, lovastatin, atorvastatin, pravastatin, fluvastatin, and related compounds were reported to decrease the intracellular ergosterol level via the inhibition of HMG1/2 in C. glabrata, C. albicans, Ustilago maydis, Trichothecium roseum, S. cerevisiae, C. neoformans, Zygomycetes, and Aspergillus spp. [370][371][372][373][374][375][376][377][378][379][380][381]. Moreover, statin therapy is associated with a reduction in oral Candida carriage in hyperlipidemic patients [382].…”
Section: Biosynthesis Of Sphingolipidsmentioning
confidence: 99%